2016
DOI: 10.7603/s40730-016-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the neutrophil extracellular trap-driven microvascular inflammation essential for diabetes vasculopathy?

Abstract: Abstract-The neutrophil extracellular traps (NETs) are defined as an extensive web consisting decondensed chromatin, which is released from activated neutrophils, as well as cytotoxic proteins, histones and microbicidal proteases that cause tissue damage. NETs contribute to endothelial damage, inflammation, thrombosis, platelet aggregation, ischemia, that are essential players in the pathobiology of diabetic complications. The objective of the review is to highlight the possible role of NETosis in early diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Clinical studies have shown that elevated levels of serum dsDNA as a marker of NETosis was correlated with the presence of CV disease, atherosclerosis, nephropathy, and PAD [54,55]. There is evidence that angiopathy that appeared prior to atherosclerotic plaque accumulation and associated with endothelial dysfunction was closely linked to apoptotic endothelial cell originated chromatin-contained micro vesicles, which are trigger of NETosis [56,57]. Furthermore, cell free dsDNA levels associated positively with morphological evidence of plaque destabilization, severity of PAD and the risk of limb ischemia, as well as CV mortality rate [57,58].…”
Section: Netosis In Vascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that elevated levels of serum dsDNA as a marker of NETosis was correlated with the presence of CV disease, atherosclerosis, nephropathy, and PAD [54,55]. There is evidence that angiopathy that appeared prior to atherosclerotic plaque accumulation and associated with endothelial dysfunction was closely linked to apoptotic endothelial cell originated chromatin-contained micro vesicles, which are trigger of NETosis [56,57]. Furthermore, cell free dsDNA levels associated positively with morphological evidence of plaque destabilization, severity of PAD and the risk of limb ischemia, as well as CV mortality rate [57,58].…”
Section: Netosis In Vascular Complicationsmentioning
confidence: 99%
“…There is evidence that angiopathy that appeared prior to atherosclerotic plaque accumulation and associated with endothelial dysfunction was closely linked to apoptotic endothelial cell originated chromatin-contained micro vesicles, which are trigger of NETosis [56,57]. Furthermore, cell free dsDNA levels associated positively with morphological evidence of plaque destabilization, severity of PAD and the risk of limb ischemia, as well as CV mortality rate [57,58]. Additionally, cell free DNA has not just cytotoxic effect, but can be a trigger of pro-thrombotic responses [59].…”
Section: Netosis In Vascular Complicationsmentioning
confidence: 99%
“…There is evidence regarding potent possibilities to improve the EPCs' capacity using various methods, i.e., aerobic exercise, lipid lowering drugs, ACE inhibitors, calcium channel blockers, antidiabetic drugs including metformin, sitagliptin [87][88][89][90][91][92]. Several mechanisms are involved in the attenuation of EPCs functionality by mentioned above approaches, i.e., increase of NO production via enhancing phosphorylated-AMP-activated protein kinase and phosphorylated-eNOS, down-regulation of high mobility group box-1 and AkT/STAT signaling leading to oxidative stress suppression, attenuation of DNA/histone methylation, inhibition of progenitor cells' apoptosis and NETosis through suppression of proprotein convertase subtilisin/kexin type 9 and Dll4/Notch signaling pathway [93][94][95]. Subsequently, improving function of EPCs in DM appears to be under control and the prevention of CV complication development could be associated with restoring of EPCs-dependent repair mechanisms [96].…”
Section: The Concept Of Impaired Cardiac and Vessel Reparation In Diabetes: Role Of Epcsmentioning
confidence: 99%
“…Several mechanisms are involved in the attenuation of EPCs functionality by mentioned above approaches, i.e. increase of NO production via enhancing phosphorylated-AMP-activated protein kinase and phosphorylated-eNOS, down-regulation of high mobility group box-1 and AkT / STAT signaling leading to oxidative stress suppression, attenuation of DNA / histone methylation, inhibition of progenitor cells' apoptosis and NETosis through suppression of proprotein convertase subtilisin/kexin type 9 and Dll4/Notch signaling pathway [76][77][78]. Subsequently, improving function of EPCs in DM appears to be under control and the prevention of CV complication development could be associated with restoring of EPCs-dependent repair mechanisms.…”
Section: The Concept Of Impaired Cardiac and Vessel Reparation In Diamentioning
confidence: 99%